Optimization of cell motility evaluation in scratch assay - Gotsulyak, N.Ya.; Kosach, V.R.; Cherednyk, O.V.; Tykhonkova, I.O.; Khoruzhenko, A.I. (Вiopolymers and Cell, 2014)
A scratch test is one of the most popular methods of classical cell migration assay in a monolayer culture. At the same time, the scratch assay has some disadvantages that can be easily corrected. Aim. Optimization the existent scratch assay on the base of detection of scratch wound surface area and the length of the field of observation which is more objective and less time consuming. Methods. Scratch assay. Results. The modification of scratch assay enables to perform measurement more accurately and rapidly. This approach is more simple and eliminates the main disadvantages of the classical method. Conclusions. The procedure of scratch wound width measurement calculated on the base of detection of cell free area and the length of the field of observation is more effective than the classical wound healing assay. It will be useful for the estimation of cell migration dynamics in monolayer culture for a wide range of live cell based experiments.